The Clinical Efficiency of Positive Airway Pressure Treatment. (29th April 2013) - Koseoglu, Sabri; Ikinciogullari, Aykut; Cetin, Mehmet Ali; Saygi Uysal, Gokce; Kum, Rauf Oguzhan; Arli, Berna
Abstract : Objectives . The aim of this study was to evaluate the clinical efficiency and compliance of positive airway pressure (PAP) treatment. Materials and Methods . This study was conducted on moderate-severe obstructive sleep apnea syndrome (OSAS) patients who admitted to Ankara Numune Hospital Sleep Center between 2008 and 2012. Seventy-five patients with moderate-severe OSAS who were using PAP treatment regularly were enrolled in the study. Patient's usage data, Epworth sleepiness scale (ESS) scores, and the differences in complaints of OSAS were recorded. Results . The overall complaints were improved when compared to pretreatment period. Particularly there was improvement in apnea, snoring, excessive daytime sleepiness, fatigue, and sleep quality. Conclusion . PAP is effective in reducing symptoms in people with moderate and severe OSAS. To inform the patients with details and the creation of strategies for close followup are necessary for improving the compliance of the patients. Trial registration number: ACTRN12613000373774.